Challenges and applications of artificial intelligence in infectious diseases and antimicrobial resistance - Angela Cesaro; Samuel C. Hoffman; Payel Das; Cesar de la Fuente-Nunez (npj Antimicrobials and Resistance)
Abstract Artificial intelligence (AI) has transformed infectious disease control, enhancing rapid diagnosis and antibiotic discovery. While conventional tests delay diagnosis, AI-driven methods like machine learning and deep learning assist in pathogen detection, resistance prediction, and drug discovery. These tools improve antibiotic stewardship and identify effective compounds such as antimicrobial peptides and small molecules. This review explores AI applications in diagnostics, therapy, and drug discovery, emphasizing both strengths and areas needing improvement.